Transforming the Workforce for Children Birth Through Age 8: A Unifying Foundation - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Children are already learning at birth, and they develop and learn at a rapid pace in their early years. This provides a critical foundation for lifelong progress, and the adults who provide for the care and the education of young children bear a great responsibility for their health, development, and learning. Despite the fact that they share the same objective - to nurture young children and secure their future success - the various practitioners who contribute to the care and the education of children from birth through age 8 are not acknowledged as a workforce unified by the common knowledge and competencies needed to do their jobs well. Transforming the Workforce for Children Birth Through Age 8 explores the science of child development, particularly looking at implications for the professionals who work with children. This report examines the current capacities and practices of the workforce, the settings in which they work, the policies and infrastructure that set qualifications and provide professional learning, and the government agencies and other funders who support and oversee these systems. This book then makes recommendations to improve the quality of professional practice and the practice environment for care and education professionals. These detailed recommendations create a blueprint for action that builds on a unifying foundation of child development and early learning, shared knowledge and competencies for care and education professionals, and principles for effective professional learning. Young children thrive and learn best when they have secure, positive relationships with adults who are knowledgeable about how to support their development and learning and are responsive to their individual progress. Transforming the Workforce for Children Birth Through Age 8 offers guidance on system changes to improve the quality of professional practice, specific actions to improve professional learning systems and workforce development, and research to continue to build the knowledge base in ways that will directly advance and inform future actions. The recommendations of this book provide an opportunity to improve the quality of the care and the education that children receive, and ultimately improve outcomes for children.
Keywords: Behavioral and Social Sciences

Improving Data on America's Aging Population: Summary of a Workshop - National Research Council (The National Academies Press, 1996)
The Committee on National Statistics and the Committee on Population, at the request of the NIA, convened a workshop in March 1996 to discuss data on the aging population that address the emerging and important social, economic, and health conditions of the older population. The purposes of the workshop were to identify how the population at older ages in the next few decades will differ from the older population today, to understand the underlying causes of those changes, to anticipate future problems and policy issues, and to suggest future needs for data for research in these areas. The scope of the workshop was broader than that of the 1988 CNSTAT report, including not only data on health and long-term care, but also actuarial, economic, demographic, housing, and epidemiological data needs for informing public policy.
Keywords: Behavioral and Social Sciences

Critical Perspectives on Schooling and Fertility in the Developing World - National Research Council (The National Academies Press, 1999)
This volume assesses the evidence, and possible mechanisms, for the associations between women's education, fertility preferences, and fertility in developing countries, and how these associations vary across regions. It discusses the implications of these associations for policies in the population, health, and education sectors, including implications for research.
Keywords: Behavioral and Social Sciences

Perspectives on the Future of the Sociology of Aging - National Research Council (The National Academies Press, 2012)
The population of the United States is growing inexorably older. With birth rates historically low and life expectancy continuing to rise, the age distribution of the population in the United States is growing steadily older. This demographic shift is occurring at a time of major economic and social changes, which have important implications for the growing elderly population. Other changes, such as the move away from defined-benefit toward defined-contribution retirement plans, changes in some corporate and municipal pension plans as a result of market pressures, and the 2008 financial crisis precipitated by the crash of the housing market, all have economic implications for older people. They are also likely to make it more difficult for certain groups of future retirees to find their retirements at the level that they had planned and would like. To deal effectively with the challenges created by population aging, it is vital to first understand these demographic, economic, and social changes and, to the extent possible, their causes, consequences, and implications. Sociology offers a knowledge base, a number of useful analytic approaches and tools, and unique theoretical perspectives that can be important aids to this task. The Panel on New Directions in Social Demography, Social Epidemiology, and the Sociology of Aging was established in August 2010 under the auspices of the Committee on Population of the National Research Council to prepare a report that evaluates the recent contributions of social demography, social epidemiology, and sociology to the study of aging and seeks to identify promising new research in these fields. Perspectives on the Future of the Sociology of Aging provides candid and critical comments that will assist the institution in making the final published volume as sound as possible and to ensure that the volume meets institutional standards for objectivity, evidence, and responsiveness to the study charge.
Keywords: Behavioral and Social Sciences

Future Directions for the Demography of Aging: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Almost 25 years have passed since the Demography of Aging (1994) was published by the National Research Council. Future Directions for the Demography of Aging is, in many ways, the successor to that original volume. The Division of Behavioral and Social Research at the National Institute on Aging (NIA) asked the National Academies of Sciences, Engineering, and Medicine to produce an authoritative guide to new directions in demography of aging. The papers published in this report were originally presented and discussed at a public workshop held in Washington, D.C., August 17-18, 2017. The workshop discussion made evident that major new advances had been made in the last two decades, but also that new trends and research directions have emerged that call for innovative conceptual, design, and measurement approaches. The report reviews these recent trends and also discusses future directions for research on a range of topics that are central to current research in the demography of aging. Looking back over the past two decades of demography of aging research shows remarkable advances in our understanding of the health and well-being of the older population. Equally exciting is that this report sets the stage for the next two decades of innovative research–a period of rapid growth in the older American population.
Keywords: Behavioral and Social Sciences

New Directions in the Sociology of Aging - National Research Council (The National Academies Press, 2013)
The aging of the population of the United States is occurring at a time of major economic and social changes. These economic changes include consideration of increases in the age of eligibility for Social Security and Medicare and possible changes in benefit levels. Furthermore, changes in the social context in which older individuals and families function may well affect the nature of key social relationships and institutions that define the environment for older persons. Sociology offers a knowledge base, a number of useful analytic approaches and tools, and unique theoretical perspectives that can facilitate understanding of these demographic, economic, and social changes and, to the extent possible, their causes, consequences and implications. New Directions in the Sociology of Aging evaluates the recent contributions of social demography, social epidemiology and sociology to the study of aging and identifies promising new research directions in these sub-fields. Included in this study are nine papers prepared by experts in sociology, demography, social genomics, public health, and other fields, that highlight the broad array of tools and perspectives that can provide the basis for further advancing the understanding of aging processes in ways that can inform policy. This report discusses the role of sociology in what is a wide-ranging and diverse field of study; a proposed three-dimensional conceptual model for studying social processes in aging over the life cycle; a review of existing databases, data needs and opportunities, primarily in the area of measurement of interhousehold and intergenerational transmission of resources, biomarkers and biosocial interactions; and a summary of roadblocks and bridges to transdisciplinary research that will affect the future directions of the field of sociology of aging.
Keywords: Behavioral and Social Sciences

Evaluation of Compensation Data Collected Through the EEO-1 Form - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The U.S. Equal Employment Opportunity Commission (EEOC) expanded EEO-1 data collection for reporting years 2017 to 2018 in an effort to improve its ability to investigate and address pay disparities between women and men and between different racial and ethnic groups. These pay disparities are well documented in national statistics. For example, the U.S. Census Bureau (2021) found that Black and Hispanic women earned only 63 percent and 55 percent as much, respectively, of what non-Hispanic White men earned. Evaluation of Compensation Data Collected Through the EEO-1 Form examines the quality of pay data collected using the EEO-1 form and provides recommendations for future data collection efforts. The report finds that there is value in the expanded EEO-1 data, which are unique among federal surveys by providing employee pay, occupation, and demographic data at the employer level. Nonetheless, both short-term and longer-term improvements are recommended to address significant concerns in employer coverage, conceptual definitions, data measurement, and collection protocols. If implemented, these recommendations could improve the breadth and strength of EEOC data for addressing pay equity, potentially reduce employer burden, and better support employer self-assessment.
Keywords: Behavioral and Social Sciences

Understanding the Aging Workforce: Defining a Research Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The aging population of the United States has significant implications for the workforce - challenging what it means to work and to retire in the U.S. In fact, by 2030, one-fifth of the population will be over age 65. This shift has significant repercussions for the economy and key social programs. Due to medical advancements and public health improvements, recent cohorts of older adults have experienced better health and increasing longevity compared to earlier cohorts. These improvements in health enable many older adults to extend their working lives. While higher labor market participation from this older workforce could soften the potential negative impacts of the aging population over the long term on economic growth and the funding of Social Security and other social programs, these trends have also occurred amidst a complicating backdrop of widening economic and social inequality that has meant that the gains in health, improvements in mortality, and access to later-life employment have been distributed unequally. Understanding the Aging Workforce: Defining a Research Agenda offers a multidisciplinary framework for conceptualizing pathways between work and nonwork at older ages. This report outlines a research agenda that highlights the need for a better understanding of the relationship between employers and older employees; how work and resource inequalities in later adulthood shape opportunities in later life; and the interface between work, health, and caregiving. The research agenda also identifies the need for research that addresses the role of workplaces in shaping work at older ages, including the role of workplace policies and practices and age discrimination in enabling or discouraging older workers to continue working or retire.
Keywords: Behavioral and Social Sciences

Demography of Aging - National Research Council (The National Academies Press, 1994)
As the United States and the rest of the world face the unprecedented challenge of aging populations, this volume draws together for the first time state-of-the-art work from the emerging field of the demography of aging. The nine chapters, written by experts from a variety of disciplines, highlight data sources and research approaches, results, and proposed strategies on a topic with major policy implications for labor forces, economic well-being, health care, and the need for social and family supports.
Keywords: Behavioral and Social Sciences; Health and Medicine

Educating One and All: Students with Disabilities and Standards-Based Reform - National Research Council (The National Academies Press, 1997)
In the movement toward standards-based education, an important question stands out: How will this reform affect the 10% of school-aged children who have disabilities and thus qualify for special education? In Educating One and All, an expert committee addresses how to reconcile common learning for all students with individualized education for "one"—the unique student. The book makes recommendations to states and communities that have adopted standards-based reform and that seek policies and practices to make reform consistent with the requirements of special education. The committee explores the ideas, implementation issues, and legislative initiatives behind the tradition of special education for people with disabilities. It investigates the policy and practice implications of the current reform movement toward high educational standards for all students. Educating One and All examines the curricula and expected outcomes of standards-based education and the educational experience of students with disabilities—and identifies points of alignment between the two areas. The volume documents the diverse population of students with disabilities and their school experiences. Because approaches to assessment and accountability are key to standards-based reforms, the committee analyzes how assessment systems currently address students with disabilities, including testing accommodations. The book addresses legal and resource implications, as well as parental participation in children's education.
Keywords: Education; Behavioral and Social Sciences

The Growing Gap in Life Expectancy by Income: Implications for Federal Programs and Policy Responses - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The U.S. population is aging. Social Security projections suggest that between 2013 and 2050, the population aged 65 and over will almost double, from 45 million to 86 million. One key driver of population aging is ongoing increases in life expectancy. Average U.S. life expectancy was 67 years for males and 73 years for females five decades ago; the averages are now 76 and 81, respectively. It has long been the case that better-educated, higher-income people enjoy longer life expectancies than less-educated, lower-income people. The causes include early life conditions, behavioral factors (such as nutrition, exercise, and smoking behaviors), stress, and access to health care services, all of which can vary across education and income. Our major entitlement programs – Medicare, Medicaid, Social Security, and Supplemental Security Income – have come to deliver disproportionately larger lifetime benefits to higher-income people because, on average, they are increasingly collecting those benefits over more years than others. This report studies the impact the growing gap in life expectancy has on the present value of lifetime benefits that people with higher or lower earnings will receive from major entitlement programs. The analysis presented in The Growing Gap in Life Expectancy by Income goes beyond an examination of the existing literature by providing the first comprehensive estimates of how lifetime benefits are affected by the changing distribution of life expectancy. The report also explores, from a lifetime benefit perspective, how the growing gap in longevity affects traditional policy analyses of reforms to the nation’s leading entitlement programs. This in-depth analysis of the economic impacts of the longevity gap will inform debate and assist decision makers, economists, and researchers.
Keywords: Behavioral and Social Sciences; Industry and Labor; Surveys and Statistics

Aging and the Macroeconomy: Long-Term Implications of an Older Population - National Research Council (The National Academies Press, 2012)
The United States is in the midst of a major demographic shift. In the coming decades, people aged 65 and over will make up an increasingly large percentage of the population: The ratio of people aged 65+ to people aged 20-64 will rise by 80%. This shift is happening for two reasons: people are living longer, and many couples are choosing to have fewer children and to have those children somewhat later in life. The resulting demographic shift will present the nation with economic challenges, both to absorb the costs and to leverage the benefits of an aging population. Aging and the Macroeconomy: Long-Term Implications of an Older Population presents the fundamental factors driving the aging of the U.S. population, as well as its societal implications and likely long-term macroeconomic effects in a global context. The report finds that, while population aging does not pose an insurmountable challenge to the nation, it is imperative that sensible policies are implemented soon to allow companies and households to respond. It offers four practical approaches for preparing resources to support the future consumption of households and for adapting to the new economic landscape.
Keywords: Behavioral and Social Sciences; Health and Medicine; Industry and Labor

Promoting the Educational Success of Children and Youth Learning English: Promising Futures - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating dual language learners (DLLs) and English learners (ELs) effectively is a national challenge with consequences both for individuals and for American society. Despite their linguistic, cognitive, and social potential, many ELs—who account for more than 9 percent of enrollment in grades K-12 in U.S. schools—are struggling to meet the requirements for academic success, and their prospects for success in postsecondary education and in the workforce are jeopardized as a result. Promoting the Educational Success of Children and Youth Learning English: Promising Futures examines how evidence based on research relevant to the development of DLLs/ELs from birth to age 21 can inform education and health policies and related practices that can result in better educational outcomes. This report makes recommendations for policy, practice, and research and data collection focused on addressing the challenges in caring for and educating DLLs/ELs from birth to grade 12.
Keywords: Education; Behavioral and Social Sciences

Key National Education Indicators: Workshop Summary - National Research Council (The National Academies Press, 2012)
The education system in the United States is continually challenged to adapt and improve, in part because its mission has become far more ambitious than it once was. At the turn of the 20th century, less than one-tenth of students enrolled were expected to graduate from high school. Today, most people expect schools to prepare all students to succeed in postsecondary education and to prosper in a complex, fast-changing global economy. Goals have broadened to include not only rigorous benchmarks in core academic subjects, but also technological literacy and the subtler capacities known as 21st-century skills. To identify the most important measures for education and other issues and provide quality data on them to the American people, Congress authorized the creation of a Key National Indicators System (KNIS). This system will be a single Web-based information source designed to help policy makers and the public better assess the position and progress of the nation across a wide range of areas. Identifying the right set of indicators for each area is not a small challenge. To serve their purpose of providing objective information that can encourage improvement and innovation, the indicators need to be valid and reliable but they also need to capture the report committee's aspirations for education. This report describes a workshop, planned under the aegis of the Board on Testing and Assessment and the Committee on National Statistics of the National Research Council. Key National Education Indicators is a summary of the meeting of a group with extensive experience in research, public policy, and practice. The goal of the workshop was not to make a final selection of indicators, but to take an important first step by clearly identifying the parameters of the challenge.
Keywords: Education; Behavioral and Social Sciences; Surveys and Statistics

The Dynamics of Disability: Measuring and Monitoring Disability for Social Security Programs - Institute of Medicine; National Research Council (The National Academies Press, 2002)
The Society Security disability program faces urgent challenges: more people receiving benefits than ever before, the prospect of even more claimants as baby boomers age, changing attitudes culminating in the Americans With Disabilities Act. Disability is now understood as a dynamic process, and Social Security must comprehend that process to plan adequately for the times ahead. The Dynamics of Disability provides expert analysis and recommendations in key areas:
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Improving Health Care Cost Projections for the Medicare Population: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
Developing credible short-term and long-term projections of Medicare health care costs is critical for public- and private-sector policy planning, but faces challenges and uncertainties. There is uncertainty not only in the underlying economic and demographic assumptions used in projection models, but also in what a policy modeler assumes about future changes in the health status of the population and the factors affecting health status , the extent and pace of scientific and technological breakthroughs in medical care, the preferences of the population for particular kinds of care, the likelihood that policy makers will alter current law and regulations, and how each of these factors relates to health care costs for the elderly population.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics